Qualitative and digital research in times of crisis : methods, reflexivity, and ethics - Kara, Helen; Khoo, Su-ming (Policy Press, 2021)
Includes contributions on qualitative and digital research from Europe, Asia, Africa, Australasia and the Americas, this volume explores the creative and thoughtful ways in which researchers have adapted methods and rethought relationships in response to challenges arising from crises such as the COVID-19 pandemic, disasters or violent conflict.